Retention of IT professionals: Examining the influence of empowerment, social exchange, and trust - Erturk, Alper; Vurgun, Levent (Elsevier Science Inc, 2015)
Given the importance of information technology professionals in today's high-technology-driven business environment, the issue of how to retain these professionals has received relatively little attention. Hence, using data from IT professionals employed in private companies in Turkey, this study explores the role of psychological empowerment, leader-member exchange, perceived organizational support and organizational trust in reducing turnover intentions of IT professionals. The results indicate that perceived organizational support fully mediates the relationship between psychological empowerment and turnover intentions, whereas leader-member exchange has a partial mediating effect on this relationship. In addition, results also yield that organizational trust moderates the mediated relationship between psychological empowerment and turnover intentions, in such a way that trust in organization moderates the mediating influence of perceived organizational support, whereas trust in supervisor moderates the mediating effect of leader-member exchange. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Psychological empowerment; Leader-member exchange; Perceived organizational support; Organizational trust; Turnover intentions; IT professionals